Penerapan model pembelajaran Creative Problem Solving (CPS) untuk meningkatkan hasil belajar siswa kelas VI SDN 02 Talun Kabupaten Pekalongan - Asep Tri Prasetiyo (Action Research Journal, 2021)
The problem in this classroom action research is whether the learning outcomes of class VI students at SDN 02 Talun, Pekalongan Regency can be improved through the implementation of creative problem solving (CPS) models? The purpose of this classroom action research is to find out whether the application of the CPS learning model can improve student learning outcomes and how the changes in the level of student activity during learning with the applied creative problem solving learning model. The subjects in this classroom action research were 28 students of class VI. This classroom action research was conducted in 2 cycles where each cycle consisted of 2 learning meetings. The indicator of the success of this research is that student learning outcomes increase if the average student learning outcomes reach an average value of 70 and the number of students who complete learning is 85%. The results of this classroom action research indicate an increase in student learning outcomes in the evaluation of cycles I and II, namely an increase in the class average value from 71.75 to 76.63 with the percentage of classical completeness in cycle I reaching 75% and cycle II reaching 89.28. %. The increase in student learning outcomes was followed by changes in the level of student activity during learning, namely the first cycle from 67.5% to 85% in the second cycle. Observation of teacher activities has increased from 75% in the first cycle to 90% in the second cycle. Based on the results of these studies, suggestions that can be given are the need to apply the CPS learning model to improve learning outcomes and student activity.